Performance of air-conditioning system with different nanoparticle composition ratio of hybrid nanolubricant - Nurul Nadia, Mohd Zawawi; Wan Hamzah, Azmi; Mohd Fairusham, Ghazali; Hafiz, Muhammad Ali (MDPI AG, 2022)
To reduce fuel consumption, the automotive air-conditioning (AAC) system’s coefficient of performance (COP) needs to be improved. The use of a diverse selection of hybrid nanolubricant composition ratios is expected to improve the properties of single nanolubricants, resulting in improved AAC system performance. The goal of this study was to find the best combination of hybrid nanolubricants for the best performance of the AAC system. Al2O3-SiO2/PAG hybrid nanolubricants at 0.06% volume concentrations with various composition ratios (20:80, 40:60, 50:50, 60:40, and 80:20) were investigated. An initial refrigerant charge of up to 155 g and a compressor speed of up to 2100 rpm were used in the experiment. The cooling capacity, compressor work, and COP of the AAC system were measured to determine its efficiency. The COP enhancement and compressor work reduction were recorded up to 16.31% and 18.65% for the 60:40 composition ratio, respectively. The maximum cooling capacity up to 75.84% was recorded for the 80:20 ratio, followed by 60:40. The maximum COP value of 8.81 for 155 g of hybrid nanolubricants was obtained at 900 rpm with a 60:40 composition ratio. Therefore, for optimal performance in the AAC system, a 60:40 composition ratio of the Al2O3-SiO2/PAG nanolubricant combination is strongly recommended.